PEMBENTUKAN NILAI KARAKTER RELIGIUS PESERTA DIDIK DI MADRASAH IBTIDAIYAH BUSTANUL ULUM KOTA BATU - Temti Lestari; Anwar Sa’dullah; Rosichin Mansur (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstrakThe research conducted by the author aims to describe: 1) Teacher's efforts in forming the value of the religious character of students in MI Bustanul Ulum Batu city, 2) Process in forming the value of the religious character of students in MI Bustanul Ulum Batu city. This study uses a type of qualitative research by seeking information from the head of the madrasa, student affairs, and also several teachers. This study also uses data collection techniques through observation, interviews, and documentation, the data are analyzed through several steps, namely data reduction, data presentation and conclusion drawing. The technique of checking the validity of data is done through data sources and methods of extending attendance, data triangulation, and peer discussions. This study shows that the formation of the value of the religious character of students is carried out and formed through routine habituation from morning to completion of learning. The elements of the formation of religious charismatic values are trust, worship, religious experience, good attitude, and responsibility for what is done. Therefore, the authors conclude that the efforts and processes carried out through routine habituation every day will be able to form the expected value of the religious character of the students. Keyword: formation, character value, religious